Household Food Insecurity and Its Association with Nutritional Status of Children 6–59 Months of Age in East Badawacho District, South Ethiopia - Betebo, Bealu (J Environ Public Health, 2017)
Background. Ethiopia has one of the highest child malnutrition rates in the world. Food insecurity is one of the determinant factors of malnutrition in developing countries; however its role remains unclear. Objective. To assess household food insecurity and its association with the nutritional status of children 6–59 months of age in East Badawacho District, South Ethiopia. Methods. A community based cross-sectional study was conducted from February 20 to 30, 2014 on a sample of 508 mother/child pairs of 6–59-month-old children. Sample households with eligible children were selected using systematic random sampling technique. Both bivariate and multivariate analysis were used to identify factors associated with nutritional status of children. P value of <0.05 was considered as statistically significant. Result. The prevalence of household food insecurity was 75.8%. The prevalence rates of stunting, underweight, and wasting among children were 45.6%, 26.3%, and 14.6%, respectively. Household food insecurity was significantly associated with underweight (AOR = 3.82; CI = 1.78–8.19) and stunting (AOR = 6.7; CI = 3.71–12.1) but not with wasting. Conclusion and Recommendation. Household food insecurity and the prevalence rates of stunting, underweight, and wasting, among children 6 to 59 months, were high. Intervention programs should focus on improving household food insecurity and nutritional status of children.